2016
DOI: 10.1596/1813-9450-7843
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Education Mobility in Africa: Has Progress been Inclusive?

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 61 publications
4
36
0
Order By: Relevance
“…Parental background influences children's educational, health and general life outcomes (Lambert et al., ). More specifically, parental educational attainment is thought to influence educational outcomes among children, particularly daughters (Azomahou & Yitbarek, ). Many graduates in the present study achieved qualifications two levels above the educational attainment of their parents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Parental background influences children's educational, health and general life outcomes (Lambert et al., ). More specifically, parental educational attainment is thought to influence educational outcomes among children, particularly daughters (Azomahou & Yitbarek, ). Many graduates in the present study achieved qualifications two levels above the educational attainment of their parents.…”
Section: Discussionmentioning
confidence: 99%
“…Low‐ and middle‐income countries (LMICs) face a compounding burden of poverty, rapid population growth, high levels of diseases and limited access to health, education and social services. Despite recent economic growth in Sub‐Saharan Africa, rising inequality (particularly for women and children) has been noted in several countries, including each of the East African nations (Azomahou & Yitbarek, ). An earlier study reported that, although Africa has a 28% share of the global burden of diseases and 13.76% of the global population, it only has a 1.3% share of health services (Simplice, ).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations